Scientific-technological society, functional diversity and equal inclusion: Ethical-political approach to the technological design of a universally accessible environment - Aparicio Payá, Manuel (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
The objective of this work, framed in the philosophical perspective of the intersection between the Disability studies and the philosophical-social studies on science and technology (CTS), is to address the issue of universal accessibility, related to design for all. I Intend to carry out an ethicalpolitical reflection on this subject, in the context of the possibilities opened by the emerging scientifictechnological development and its repercussions in relation to the groups of people with different types of functional diversity.